Actor training the Laban way : an integrated approach to voice, speech, and movement - Adrian, Barbara (Allworth Press, 2008)
Actors can improve their skills and become more expressive in body and voice by following the teachings of the author of this book, one of the most important movement theorists of the twentieth century. This in depth, fully illustrated guide offers a groundbreaking approach to understanding physical and vocal movement that will enable readers to discover how to maximize their potential. Packed with practical exercises for individuals, partners, and group work, this book integrates voice, speech, and movement. Exercises for breath support, tone, range, articulation, dynamic alignment, balance, flexibility, strength, and stamina, as well as building relationships, this book is essential reading for all serious actors, acting teachers, and students.